Energy use and global warming potential: evaluating diverse cropping systems. A field study in Chapainawabganj District in Bangladesh - Saiful Islam; Cheesman, Stephanie; Maruf Hossen Shanto; Md. Arifur Rahaman; Hossain, M. Khaled; Sarker, Palash; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
The Barind Tract, located in the Chapainawabganj region of Bangladesh, spans 13,311 hectares of net cropped area (DAE 2023) and is characterized by a challenging agroecological environment. The areas are victim to high temperatures, limited soil moisture retention, and erratic, low rainfall, contributing to severe water stress. The region’s soils are known for their poor drainage, low organic matter content, and susceptibility to drought, all leading to suboptimal crop productivity (Ali et al. 2018; Harun et al. 2017). In this context, addressing these issues through sustainable agricultural practices is crucial to enhance both productivity and resilience in the face of climate change. To tackle the agronomic challenges in Chapainawabganj, a participatory research trial was conducted from 2022 to 2023. The study explored diversified, intensified, and climate-resilient cropping system options, comparing them with traditional farming practices in the region. This brief highlights the key findings on energy use, global warming potential, and emission intensity from the study, offering insights into viable solutions for improving agricultural outcomes in this climate-sensitive area.